Poland: Employment Relationship from the Perspective of Individual, Collective Labor Law and EU Law - Barański, Michał (Fundamentals of Labor Law in Central Europe, 2022)
In Poland, labor law is now an independent branch of law (within a uniform legal system). The employment relationship is a central concept in Polish labor law. This relationship has a specific legal character, which distinguishes it, e.g., from civil law, administrative law, and criminal law relationships. In the Polish legal order, employment does not must have an employee character (within the employment relationship). This chapter is devoted to Polish national regulations concerning employment contracts and collective labor agreements, with particular emphasis on their power to shape legal relationships. The content of the chapter shows the relationship between the individual and collective labor law. An analysis has been made of the compliance of Polish regulations on employment relationships with EU law. It also presents selected current regulatory issues of Polish labor law through the prism of issues concerning the formative power of an employment contract and a collective agreement (in terms of the impact of COVID-19 and automation on employment relationship regulations). Keywords: employment contracts, collective agreements, Poland, labor law, EU law, COVID-19, automation